Morfologi trikoma dan respons terhadap stres biotik pada tanaman cabai rawit dengan perlakuan pupuk organik - Nurul Chairiyah; Aditya Murtilaksono; Nurjannah; Muh. Adiwena; Muttaqien; Siti Agustia Lastari (Jurnal Penelitian Pendidikan IPA, 2025)
Trichomes play a role in protecting plants from herbivores and pathogens, and their formation can be influenced by nutrient availability and environmental factors. This study examined the effect of liquid organic fertilizer (POC) on the development of leaf trichomes in cayenne pepper (Capsicum frutescens) grown on ultisol soil in Tarakan, Indonesia. The experiment used a completely randomized design with seven fertilization treatments: control (P0), NPK (P1), and POC at concentrations of 5–15 g/L (P2–P6), each replicated four times. Leaf samples collected 45 days after transplanting were cleared, stained, and observed microscopically. Several types of trichomes were identified, with non-glandular forms observed more frequently than glandular ones, mainly located along the abaxial midrib and veins. Variation in trichome number and form appeared to increase in plants treated with higher POC concentrations (10–15 g/L). Occasional fungal structures were noted on some leaf surfaces, coinciding with the presence of glandular trichomes. These observations suggest that POC application may influence trichome development in cayenne pepper under field conditions, providing preliminary morphological information relevant to organic fertilization practices on marginal soils.